2017
DOI: 10.3171/2016.4.jns1624
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic versus deterministic tractography for delineation of the cortico-subthalamic hyperdirect pathway in patients with Parkinson disease selected for deep brain stimulation

Abstract: OBJECTIVE Diffusion-weighted MRI (DWI) and tractography allows noninvasive mapping of the structural connections of the brain, and may provide important information for neurosurgical planning. The hyperdirect pathway, connecting the subthalamic nucleus (STN) with the motor cortex, is assumed to play a key role in mediating the effects of deep brain stimulation (DBS), which is an effective but poorly understood treatment for Parkinson disease. This study aimed to apply recent methodological advances in DWI acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 52 publications
2
81
0
2
Order By: Relevance
“…In addition, the modulation of the hyperdirect pathway between the STN and cortical regions was postulated (115). A recent study using diffusion MRI-based tractography (both deterministic and probabilistic) showed that the connections from ipsilateral motor cortex primarily terminated in the dorsolateral STN, further highlighting a key role of hyperdirect pathways in mediating the effects of DBS (116). A diffusion tensor imaging (DTI) analysis investigating the connectivity map of GPi revealed the anterior part to be mainly connected to the prefrontal cortex, the middle section to the brainstem and GPe and the dorsal GPi mainly to the thalamus and GPe (117).…”
Section: Network Effects Of Dbsmentioning
confidence: 99%
“…In addition, the modulation of the hyperdirect pathway between the STN and cortical regions was postulated (115). A recent study using diffusion MRI-based tractography (both deterministic and probabilistic) showed that the connections from ipsilateral motor cortex primarily terminated in the dorsolateral STN, further highlighting a key role of hyperdirect pathways in mediating the effects of DBS (116). A diffusion tensor imaging (DTI) analysis investigating the connectivity map of GPi revealed the anterior part to be mainly connected to the prefrontal cortex, the middle section to the brainstem and GPe and the dorsal GPi mainly to the thalamus and GPe (117).…”
Section: Network Effects Of Dbsmentioning
confidence: 99%
“…While the probabilistic approach is time intensive, the data-driven nature may be more practical and provide advantages over a manual iterative approach. Moreover, probabilistic tractography provides more consistent and plausible tractography results that deterministic tractography (Petersen et al, 2016). Still, there are studies that controvert the reliability of diffusion tractography, whether using deterministic or probabilistic methods, for reproducing known anatomy, with results highly dependent on data quality, the algorithm selected, and the parameter settings (Thomas et al, 2014; Knösche et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…Such a pathway has now also been shown in humans (Fernandez-Miranda et al, 2012;Petersen et al, 2017). Dopamine effects, on the other hand, could be driven via nigro-striatal input going into the basal ganglia structures at the subcortical level while also affecting the oscillatory dynamics between the inhibitory interneurons and the excitatory pyramidal neurons at the cortical level and thus affecting the corticospinal drive.…”
Section: Study IIImentioning
confidence: 96%
“…Striatum is the main input nucleus in the BG system receiving glutamatergic (excitatory) inputs from several parts of the cerebral cortex (Bolam et al, 2000;Hammond et al, 2007;Utter and Basso, 2008). Recent evidence also shows that the STN receives wide excitatory connections from the cortical areas including the motor cortex via the so-called hyperdirect pathway (Nambu et al, 2000;Fernandez-Miranda et al, 2012;Petersen et al, 2017). Striatum receives dopaminergic innervation from substantia nigra pars compacta (SNc) while the ventral tegmental area (VTA) projects to limbic and frontal cortex, both nuclei with a large proportion of dopaminergic neuronal populations.…”
Section: Basal Ganglia-cortical Circuitrymentioning
confidence: 99%
See 1 more Smart Citation